2019
DOI: 10.2903/j.efsa.2019.5780
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate age range for introduction of complementary feeding into an infant's diet

Abstract: Following a request from the European Commission, the Panel on Nutrition, Novel

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(119 citation statements)
references
References 364 publications
(936 reference statements)
3
111
0
5
Order By: Relevance
“…A recent survey, promoted by the Italian Society of Pediatrics and conducted among primary care pediatricians, showed the wide variability in the time of preterms' introduction to complementary feeding and the type of foods proposed [10]. The European Food Safety Authority (EFSA) Panel on Nutrition recently underlined the lack of evidence [44], reporting a single randomized controlled trial (RCT) that concluded that weaning at 4 vs. 6 months corrected age does not affect anthropometric measures at 12 months corrected age in preterm infants <34 weeks of gestation [33]. However, the Panel raised doubts on the generalizability of these results to the European setting, given the specific characteristics of the population considered by Gupta et al's RCT.…”
Section: Nutrition During Weaning In Preterm Infantsmentioning
confidence: 99%
“…A recent survey, promoted by the Italian Society of Pediatrics and conducted among primary care pediatricians, showed the wide variability in the time of preterms' introduction to complementary feeding and the type of foods proposed [10]. The European Food Safety Authority (EFSA) Panel on Nutrition recently underlined the lack of evidence [44], reporting a single randomized controlled trial (RCT) that concluded that weaning at 4 vs. 6 months corrected age does not affect anthropometric measures at 12 months corrected age in preterm infants <34 weeks of gestation [33]. However, the Panel raised doubts on the generalizability of these results to the European setting, given the specific characteristics of the population considered by Gupta et al's RCT.…”
Section: Nutrition During Weaning In Preterm Infantsmentioning
confidence: 99%
“…The World Health Organization (WHO) recommends exclusively breastfeeding infants up to six months of age and introducing complementary foods thereafter [ 18 ]. The European Food and Safety Authority (EFSA) and the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) support the desirable goal to exclusively breastfeed until six months of age, as recommended by the WHO, however they elaborate on the possibilities to introduce complementary foods between the age of four and six months [ 19 , 20 , 21 ]. The EFSA recently concluded that no precise age for the start of complementary feeding can be determined, as this heavily depends on the infant’s characteristics and development [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The European Food and Safety Authority (EFSA) and the European Society for Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN) support the desirable goal to exclusively breastfeed until six months of age, as recommended by the WHO, however they elaborate on the possibilities to introduce complementary foods between the age of four and six months [ 19 , 20 , 21 ]. The EFSA recently concluded that no precise age for the start of complementary feeding can be determined, as this heavily depends on the infant’s characteristics and development [ 21 ]. In particular, they highlight that “Most infants do not need complementary foods for nutritional reasons up to around six months of age, with the exception of some infants at risk of iron depletion” (p. 5) and “that an infant might be developmentally ready for complementary foods before six months does not imply that this is necessary or desirable” (p. 5) [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, pediatric organizations and government bodies in Europe, such as the European Food Safety Authority, consider this definition unhelpful and even confusing. Given that many infants receive formula during the 1st year of life either alongside breastfeeding or as the sole diet, in Europe, complementary foods are generally defined as all solid and liquid foods provided to infants other than breastmilk, or infant and follow-on formula (14)(15)(16)(17). From a pediatric perspective, homemade and commercial complementary foods are meant to be provided alongside breastfeeding and not as a replacement for breastfeeding, and hence, these are not considered as BMSs.…”
Section: Our Positionmentioning
confidence: 99%